Electrically insulating PBO/MXene film with superior thermal conductivity, mechanical properties, thermal stability, and flame retardancy - Liu, Yong; Zou, Weizhi; Zhao, Ning; Xu, Jian (Nature communications, 2023)
Constructing flexible and robust thermally conductive but electrically insulating composite films for efficient and safe thermal management has always been a sought-after research topic. Herein, a nacre-inspired high-performance poly(p-phenylene-2,6-benzobisoxazole) (PBO)/MXene nanocomposite film was prepared by a sol-gel-film conversion method with a homogeneous gelation process. Because of the as-formed optimized brick and mortar structure, and the strong bridging and caging effects of the fine PBO nanofibre network on the MXene nanosheets, the resulting nanocomposite film is electrically insulating (2.5 × 10 9 Ω cm), and exhibits excellent mechanical properties (tensile strength of 416.7 MPa, Young’s modulus of 9.1 GPa and toughness of 97.3 MJ m −3 ). More importantly, the synergistic orientation of PBO nanofibres and MXene nanosheets endows the film with an in-plane thermal conductivity of 42.2 W m −1 K −1 . The film also exhibits excellent thermal stability and flame retardancy. This work broadens the ideas for preparing high-performance thermally conductive but electrically insulating composites. Constructing thermally conductive but electrically insulating composites remains a challenge. Here, Ti 3 C 2 MXene is combined in a nacre-like structure with the polymer PBO to form such materials, also exhibiting high thermal stability and flame retardancy.